2012
DOI: 10.1590/s1806-83242012005000007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 153 cases of odontogenic cysts in a South Indian sample population: a retrospective study over a decade

Abstract: Analysis of 153 cases of odontogenic cysts in a South Indian sample population: a retrospective study over a decade Abstract: The purpose of this study was to determine the prevalence of odontogenic cysts and to identify their clinico-pathological features among patients by studying biopsy specimens obtained from the archives of the Department of Oral and Maxillofacial Pathology, College of Dental Sciences, Davangere, Karnataka, India, during the past 10 years. Data for the study were retrieved from the case r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
39
2
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 13 publications
16
39
2
10
Order By: Relevance
“…The DC is the second most common odontogenic cyst in adults and the most common in children [15]. The study of Selvamani et al [1] determined the prevalence of odontogenic cysts in a South Indian sample population and found that the DC was the second more frequent cyst, after the periapical or radicular cyst. The majority of cases were reported in the second decade of life and they were more commonly seen in the anterior maxilla of males associated with erupted, developing, or impacted tooth.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The DC is the second most common odontogenic cyst in adults and the most common in children [15]. The study of Selvamani et al [1] determined the prevalence of odontogenic cysts in a South Indian sample population and found that the DC was the second more frequent cyst, after the periapical or radicular cyst. The majority of cases were reported in the second decade of life and they were more commonly seen in the anterior maxilla of males associated with erupted, developing, or impacted tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Odontogenic cysts are frequently seen in dental practice and constitute an important group of oral and maxillofacial pathology [1]. However, the frequency of odontogenic cysts in children is relatively low [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations